Investigation on Springback Behavior of Cu/Ni Clad Foils during Flexible Die Micro V-Bending Process - Chuanjie Wang; Shan Wang; Shuting Wang; Gang Chen; Peng Zhang (Metals, 2019)
With the increasing demand for micro parts using metal laminates in modern production, the manufacturing processes of thin sheet parts have been elevated. However, it is difficult to predict the deformation behavior with miniaturization because of size effects in micro-scale. In this study, the flexible die micro V-bending behavior of Cu/Ni clad foils was investigated. The bending experiments with three different punch angles and Cu/Ni clad foils under different annealed temperatures were performed. The results show that the springback angle increases with the increase of bending angle and annealing temperature. The placement of Cu/Ni clad foils induced compressive stress results in the more obvious thinning of thickness and decreasing of springback angle. The interactive effects of the distribution of deformation zones and compressive stress induced by the interface layer result in the springback behavior of Cu/Ni clad foils during the flexible die micro V-bending process.